Assessing the legal duty to use or disclose interim data for ongoing clinical trials. Issue 1 (13th August 2019) - Eckstein, Lisa
Abstract: Randomized controlled clinical trials, leading to large-scale meta-analyses, are considered the gold standard for research evaluating new drugs and other therapeutic interventions. To promote scientific integrity and prevent the adoption of potentially fallacious early trends, emerging information is commonly shielded from sponsors, investigators, and other clinical trial actors, including through the use of independent Data and Safety Monitoring Boards (DSMBs). Once established, a DSMB is usually the only body to have access to unblinded information until trial completion or the crossing of pre-specified, and often highly stringent, stopping boundaries. Yet, in certain circumstances, clinical trial actors have legal obligations to trial participants and others to use or disclose emerging information. This paper canvasses potential legal obligations to use or disclose emerging clinical trial data, including through tort law and securities laws. The analysis is supplemented by a comprehensive search of US cases in which courts have adjudicated upon such allegations. Notably, available cases demonstrate widespread judicial deference to clinical trial practices designed to shield clinical trial actors from emerging information. As a result, despite a theoretical possibility of legal obligations of use or disclosure, it appears that these will rarely be enforceable.